PENILAIAN POSISI BACKGROUND DAN BIODISTRIBUSI PADA TIROID SCAN DENGAN METODE UPTAKE - Mukmin, Amril; Za’im, Muhammad; Fakhrurreza, Muhammad; Dewi, Sofie Nornalita (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The study was conducted at RSPAD Gatoet Soebroto with activity measurement method using dose calibrator and counting gamma cameras with ROI (region of interest) technique in the total thyroid area and outside the thyroid gland called background. With sample of 30 people, the age range is 25-60 years with clinical hyperthyroidism. The thyroid gland is performed by injecting Tc-99m pertechnetate as much as 3-5 mCi intravenously, then imaging the thyroid gland for 10-15 minutes after injection using a dual headspect gamma camera. The purpose of this study was to determine the effect of position change, background ROI distance and radioisotope biodistribution on the Tc-99m pertechnetate uptake value on thyroid scan examination. The results showed the percentage of thyroid uptake at distance of 2 cm various background positions obtained mean 24.106 ± 3.476%, at distance of 4 cm various background positions were obtained averaging 24,107 ± 3,476% and at distance of 6 cm various background positions obtained a mean of 24,108 ± 3,476%. While biodistribution showed in the area of the thyroid gland and surrounding salivary glands in hyperthyroid disease, the mean value of the thyroid gland was 562293.167 ± 122587,58 count, the pharynx was obtained at an average of 23344,36 ± 13573,35 count, on the right mandible was obtained at 8745,66 ± 4200,01 count, and the left mandible obtained a mean of 9610.66 ± 4479.10 count. The relationship between percentage of thyroid uptake in the background of 2 cm and thyroid hormone levels is shown in the equation line Y (T3) = - 0.1586X + 6.3315 (r = - 0.5378 where the relationship is strong and meaningful p = 0.0580), Y (FT4) = 0, 9374X - 16,738 (r=0.5118 strong relationship, and means p = 0.0738), and Y (TSH) = 0.1775X - 2.2629 (r = 0.1715 weak relationship and not meaningful p = 0.5754). In conclusion there is a strong relationship between the percentage of uptake with thyroid hormone T3 and FT4, on the contrary a weak relationship with TSH hormone.